2020
DOI: 10.1155/2020/8881840
|View full text |Cite
|
Sign up to set email alerts
|

Acute Spontaneous Perforation of Rectosigmoid Junction in a Patient with Quadriplegia following Spinal Cord Injury

Abstract: Background. Patients with cervical spinal injury with quadriplegia are at an increased risk of developing serious gastrointestinal complications. We report an unusual case of spontaneous rectosigmoid perforation in a quadriplegic patient. Case Presentation. A 58-year-old man with diabetes mellitus and hypertension presented to the emergency department following a fall from 25 feet of height. He sustained a fifth cervical vertebral fracture with quadriplegia and neurogenic shock. One week later, he developed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It was reported that the risk of natural perforation secondary to paralytic enteritis is 3%, and the mortality rate is 50% [ 3 ]. Additionally, recent articles in the literature have reported that ischemia at the rectosigmoid junction is precipitated by multiple factors and might be a possible reason for the spontaneous perforation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that the risk of natural perforation secondary to paralytic enteritis is 3%, and the mortality rate is 50% [ 3 ]. Additionally, recent articles in the literature have reported that ischemia at the rectosigmoid junction is precipitated by multiple factors and might be a possible reason for the spontaneous perforation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…served [5]. A recent case report documented an occurrence of acute spontaneous perforation at the rectosigmoid junction in a patient with quadriplegia following a spinal cord injury [6]. Moreover, sacral root palsy related to cauda equina syndrome (CES) can lead to deterioration of fecal impaction [7].…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation